The Impact of Socio-Economic Factors on the Willingness of the Population to Maintain and Accumulate Health Capital - L. S. Spankulova; Y. Nuruly; A. R. Kerimbayev; A. Sh. Aimakhanova (Экономика: стратегия и практика)
Purpose of the article is to identify the relationship between willingness to support, family living standards and individual’s health self-assessment within the framework of the Kazakhstani population participation of in health insurance. The empirical basis of the study was the archive of sociological survey data, which is based on the population responses, taking into account the opinions in the pharmaceutical industry experts, medical workers and specialists in the insurance market. The results of the statistical analysis showed the presence of significant links between “Willingness to support” and “Self-assessment of individual health”, between “Willingness to support” and “Average monthly income per capita in the family”, as well as between “Willingness to support” and “Family living standards”. It was also found that the willingness to support is different for different strata of the population: among the population with a high self-assessment of health, a high standard of living and a high level of per capita income in the family, it is higher. In addition, the article analyzes the current state of health insurance market in the Republic of Kazakhstan, where, as a result, it was revealed that due to quarantine measures, the number of concluded insurance contracts has almost halved. The results obtained can be used by authorized state bodies in the development of health insurance programs, as well as measures to ensure the safety of the health care system of the Republic of Kazakhstan and policies in the field of effective health care.